Botanical Knowledge in the Law Enforcement: a Preliminary Approach Towards its Potential Use in Brazilian Criminal Caseworks - Manvailer, Vinicius; Leandro, Thales [UNESP]; Scremin-Dias, Edna (Inst Tecnologia Parana, 2018)
We surveyed Brazilian forensic institutes in order to provide a baseline for botanical knowledge used in forensic applications. Our approach provides a better understanding of the law enforcement dynamics as a whole, and establishes perspectives and guidelines for implementing this discipline in Brazil, enhancing the elucidative power of Brazilian forensic institutes.
Keywords: Botany; Criminal Investigation; Criminalistics; Forensic Sciences; Plant Sciences